Political Propaganda Of 2024 Election In Dirty Vote Movie (Van Dijk's Critical Discourse Analysis) - Khumaeroh, Eroh; Tomi Saputra, Faisal; Irianti, Een (LINGUA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
Abstract The development of movies in Indonesia is very diverse, ranging from fiction to documentaries. In 2024, Indonesia was shocked by one of the documentary films that was beyond people's expectations. The movie was titled "Dirty Vote" and directed by Dandhy Laksono. This movie has generated controversy and sparked various public opinions in the community. The purpose of this research is to find out and dig deeper into the movie "Dirty Vote" and whether there are elements implied as propaganda or not. This research uses a critical paradigm and the method used is qualitative with Teun A. Van Dijk's discourse theory model. The results show that although this movie is to educate the public, the production and distribution process is inseparable from the interests of the media to seek profits in the form of increasing the existence of the media and also the target audience. The power formed is a social movement to watch and discuss the Dirty Vote movie. Researchers found propaganda in this film in the form of spreading the ideology of patriotism or nationalism to attract public attention and influence public opinion so as not to vote for certain candidate pairs and spread hatred towards the government. The implication of this research is to open a new paradigm about a movie so that people become critical and open to the messages conveyed in mass media.